2015
DOI: 10.2214/ajr.14.13672
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Radiologist Characteristics Associated With Accuracy of Two Types of Diagnostic Mammograms

Abstract: Objective Earlier studies of diagnostic mammography found wide unexplained variability in accuracy among radiologists. We assessed patient and radiologist characteristics associated with the interpretive performance of two types of diagnostic mammography. Materials and Methods Radiologists interpreting mammograms in seven regions of the United States were invited to participate in a survey that collected information on their demographics, practice setting, breast imaging experience, and self-reported interpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…In our analysis of facility characteristics, community practices were more likely to utilize subdivisions in their category 4 examinations ( P < .001). This may appear contradictory to prior reports that emphasized the role of subspecialization in adherence to BI-RADS; a characteristic commonly associated with academics (17,22,23,25). In a study by Miglioretti et al (20), association with an academic institution was the strongest predictor of improved diagnostic accuracy.…”
Section: Discussioncontrasting
confidence: 91%
“…In our analysis of facility characteristics, community practices were more likely to utilize subdivisions in their category 4 examinations ( P < .001). This may appear contradictory to prior reports that emphasized the role of subspecialization in adherence to BI-RADS; a characteristic commonly associated with academics (17,22,23,25). In a study by Miglioretti et al (20), association with an academic institution was the strongest predictor of improved diagnostic accuracy.…”
Section: Discussioncontrasting
confidence: 91%
“…A more comprehensive reader characteristics can also be collected from readers and fed into the model to improve the accuracy of the model. For example, whether working fulltime or part-time [11] or being affiliated with academic centres [38] could affect the performance. The current study is a proof-of-concept study and although the proposed machine learning model outperformed the baseline model for categorising high-and low-performing readers, the added benefits of the variables describing additional case and reader characteristics can be explored in the future works.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the fact that the evaluating specialist has long experience in BI-RADS for breast radiology, we believe in the accuracy of the categorical decisions made (34). As a matter of fact, the studies performed have shown that factors influencing correct decision-making in BI-RADS include the experience of radiologist, his/her interest in dense breast radiology and the high number of studies s/he evaluates on an annual basis (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%